Mitigation of climate change impacts by intensive rainwater harvesting, unproductive waste lands development and intensive plantations in a vulnerable semi-arid ecosystem of Rajasthan - GREWAL, S.S. (Journal of Soil and Water Conservation, 2025)
Aravalis are considered as one of the most degraded ecosystems of India. Harsh climate, low and erratic rainfall, thirsty and hungry sandy soils, fuel, fodder and water scarcity characterize the bio-physical setting of this arid region forming northern edge of the Thar Desert. Irrigated agriculture expanded disregarding low rainfall and limited scope of groundwater recharge. The introduction of wheat and vegetable crops against Pennisetum glaucum (Pearl Millet) and Brasica nigra (Mustard) the native crops of the region led to drastic fall in water table necessitating the installation of submersible motors replacing diesel engines. The traditional wells also started drying up. Under such a scenario large number of blocks was declared as dark zones. The Sri Ram Fibres (SRF) Pvt. Limited a corporate of repute established their chemical plant in Tijara block of Alwar district of Rajasthan. The SRF was charged with the responsibility to recharge ground water double the amount of water what they would extract for approval. SRF funded a Natural Resource Management (NRM) project in 35 villages situated around the plant with sharp focus on rainwater harvesting and ground water recharge. In this implementation model, corporate funding under Corporate Social Responsibility (CSR), the execution by a grass root NGO and evaluation, impact assessment and documentation by a professional group were the unique features. In a period from 2006 to 2023, 214 earthen dams were constructed to harvest rainwater from Aravali hills, 1850 ha of privately owned wastelands were leveled and terraced and put to crops adopting in situ rainwater harvesting. More than 450 fruit and fodder plants were planted on the reclaimed lands to improve the desiccating ecology of the project villages. The reservoirs of 35 representative dams were selected for detailed reservoir survey to find storage capacities, rain gauges were installed in seven study villages and also well observations were recorded from 40 observation wells to monitor the change in groundwater table. After the construction of dams in the upper areas almost all types of lands were leveled by the farmers and put to pearl millet and mustard crops which resulted in increased income and saving in water. The improved availability of green and dry fodder from reclaimed land reduced the livestock dependence on forest land and the number of cows and goats were reduced in favor of good breed buffaloes and farmers adopted dairying as a remunerative subsidiary occupation. The promotion of sprinkler and drip irrigation system resulted in 60 to 70 percent saving of irrigation water. Total cumulative groundwater recharge from 2006-07 to 2022-23 was 3262.11 ha-m. An oasis of green cover developed in the erstwhile barren lands and improved the overall ecology of the area. The ecosystem faced different climate change related challenges and an attempt was made to mitigate those challenges. The results of attempted innovations are presented in this paper.